Five have plenty of fun - Blyton, Enid (Hodder Children's London, 2010)
George is not pleased when Berta, a spoilt American girl, turns up at Kirrin Cottage in the middle of the night - dressed in disguise! She is in hiding from kidnappers, and needs help. The Famous Five are the only ones who can protect her - but will they risk danger to themselves to help out a virtual stranger?